1994
DOI: 10.19182/remvt.9085
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichiose canine en Tunisie. Enquête séroépidémiologique

Abstract: La séroprévalence de l'ehrlichiose a été recherchée sur 1 216 chiens de 8 zones administratives situées dans 5 régions à climat différent. Dans la zone de Tunis au sens large, où l'entretien des animaux est satisfaisant, elle est de 49 % en moyenne alors qu'elle varie entre 75 et 85 % dans les autres régions de l'intérieur. Les auteurs soulignent l'importance de cette maladie et décrivent les conditions favorables à sa transmission tout en ajoutant que le pourcentage élevé de porteurs asymptomatiques prouve, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…3,4 Ehrlichia canis is an obligate intracellular bacterium infecting mononuclear cells. 29 However, in our study, inclusions were observed in erythrocytes (Figure 1e). Therefore, further studies are needed to confirm whether these inclusions correspond to E. canis bacteria or to other microorganisms not investigated in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…3,4 Ehrlichia canis is an obligate intracellular bacterium infecting mononuclear cells. 29 However, in our study, inclusions were observed in erythrocytes (Figure 1e). Therefore, further studies are needed to confirm whether these inclusions correspond to E. canis bacteria or to other microorganisms not investigated in this study.…”
Section: Discussioncontrasting
confidence: 64%